La Declaración Universal de los derechos del hombre: En el cuadro de la presente Organización Internacional - Cereceda, Raúl (Gregorianum, 1979)
Introduction: Now thirty years after the signing of the Universal Declaration of Human Rights, violations of the Declaration have increased in number and in degree in spite of the intense legal work that has been accomplished by international organizations during this same period. First part: The immediate antecedents of the Declaration, that is to say, the four freedoms speech of President Franklin D. Roosevelt; the Atlantic Charter; the Declaration of the United Nations; the San Francisco Conference which approved the U. N. Charter. Second part: The Universal Declaration of Human Rights, prepared mainly by the human rights commission under the supervision of the Socio-Economic Council of the United Nations Organization. The content of the Declaration: freedom for the individual and for the family; cultural, economic and social rights; approved by the General Assembly in Paris, December 10th, 1948. Third part: A critical judgment of the content in view of the short-comings of the United Nations Organization and its member states and of public opinion which has failed to urge the implementation of the Declaration through the mass media.